Male-to-Female Ratios, Race/Ethnicity, and Spontaneous Preterm Birth among 11 Million California Infants - Shaw, Gary M.; Mayo, Jonathan A.; Eisenberg, Michael L.; Catalano, Ralph; Stevenson, David K. (American Journal of Perinatology, 2019)
Objective An observed disparity in population-scale data are a larger number of males among preterm births (PTBs). We investigated spontaneous PTB risk among women of various race/ethnic groups in combination with infants' sex.Study Design This observational study was conducted in > 10 million California births (1991–2012) using birth certificates linked with maternal and infant hospital discharge data.Results Male-to-female ratios among term (37–42 weeks) infants exhibited the narrow ratio range 1.02 to 1.06 across race/ethnic groups. Such ratios among spontaneous PTBs were generally larger for all race/ethnic groups except non-Hispanic blacks. For blacks, ratios tended to be lower and similar to their term birth counterpart, 1.03. Hazard ratios adjusted for maternal age and education for non-Hispanic blacks were 0.99 (95% confidence interval [CI] 0.90–1.09), 1.01 (95% CI 0.95–1.08), 0.98 (95% CI 0.94–1.03), and 1.03 (95% CI 1.01–1.05), respectively, for gestational week groupings of 20 to 23, 24 to 27, 28 to 321, and 32 to 36. Hazard ratios for non-Hispanic whites for the same groupings were 1.08 (95% CI 0.98–1.18), 1.13 (95% CI 1.07–1.19), 1.21 (95% CI 1.17–1.25), and 1.18 (95% CI 1.17–1.19).Conclusion Why male-to-female ratios are similar across gestational ages in blacks but substantially higher in other race/ethnic groups is theoretically considered relative to inflammation, stress, and other influences.
Keywords: secondary sex ratio; disparity; prematurity; pregnancy